Critical Perspectives on the Crisis of Global Governance
XIX, 246 p.
Keywords: The contributors highlight alternative imaginaries and social forces harnessing new organizational and political forms to counter and displace dominant strategies of rule. They suggest that to address intensifying economic, ecological and ethical crises far more effective, legitimate and far-sighted forms of global governance are required.